Synthesis and Evaluation of Anticonvulsant Activity of Some Schiff Bases of 7-Amino-1,3-dihydro-2H-1,4-benzodiazepin-2-one - Nilkanth, Pankaj R; Ghorai, Sujit K; Sathiyanarayanan, Arulmozhi; Dhawale, Kiran; Ahamad, Tansir; Gawande, Manoj B; Shelke, Sharad N (Chemistry & biodiversity, 2020)
A variety of 1,3-dihydro-2H-1,4-benzodiazepin-2-one azomethines and 1,3-dihydro-2H-1,4-benzodiazepin-2-one benzamide were prepared, characterized and evaluated for the anticonvulsant activity in the rat using picrotoxin-induced seizure model. The prepared 1,3-dihydro-2H-1,4-benzodiazepin-2-one azomethine derivatives emerged potentially anticonvulsant molecular scaffolds exemplified by compounds, 7-{(E)-[(4-nitrophenyl)methylidene]amino}-5-phenyl-1,3-dihydro-2H-1,4-benzodiazepin-2-one, 7-[(E)-{[4-(dimethylamino)phenyl]methylidene}amino]-5-phenyl-1,3-dihydro-2H-1,4-benzodiazepin-2-one, 7-{(E)-[(4-bromo-2,6-difluorophenyl)methylidene]amino}-5-phenyl-1,3-dihydro-2H-1,4-benzodiazepin-2-one and 7-[(E)-{[3-(4-fluorophenyl)-1-phenyl-1H-pyrazol-4-yl]methylidene}amino]-5-phenyl-1,3-dihydro-2H-1,4-benzodiazepin-2-one. All these four compounds have shown substantial decrease in the wet dog shake numbers and grade of convulsions with respect to the standard drug diazepam. The most active compound, 7-[(E)-{[4-(dimethylamino)phenyl]methylidene}amino]-5-phenyl-1,3-dihydro-2H-1,4-benzodiazepin-2-one, exhibited 74 % protection against convulsion which was higher than the standard drug diazepam. Furthermore, to identify the binding mode of the interaction amongst the target analogs and binding site of the benzodiazepine receptor, molecular docking study and molecular dynamic simulation were carried out. Additionally, in silico pharmacokinetic and toxicity predictions of target compounds were carried out using AdmetSAR tool. Results of ADMET studies suggest that the pharmacokinetic parameters of all the target compounds were within the acceptable range to become a potential drug candidate as antiepileptic agents.
Keywords: potkani Wistar; Models, Molecular; Picrotoxin; zvířata; Male; Female; anticonvulsant; azepiny; pikrotoxin; Molecular Structure; Behavior, Animal; molekulární modely; Schiffovy báze; Azepines; molekulární struktura; Animals; mužské pohlaví; krysa rodu Rattus; Rats; antikonvulziva; Rats, Wistar; ženské pohlaví; Schiff Bases; záchvaty; epilepsy; molecular docking; Anticonvulsants; Seizures; chování zvířat; 1,3-dihydro-2H-1,4-benzodiazepin-2-ones; azomethine